The Effect of Self-Disclosure on Life Satisfaction and Emotions - Sabır, Safarlı; Çetinkaya, Bünyamin (Ordu Üniversitesi, 2025)
Self-disclosure plays a crucial role in fostering meaningful and healthy interpersonal relationships, enhancing both self-awareness and others’ understanding of the individual. Moreover, self-disclosure has been linked to life satisfaction and emotional experiences. This study aimed to examine the relationship between self-disclosure, life satisfaction, and emotions among university students. The study employed a relational survey model, a type of general survey design. The sample consisted of education faculty students (N = 430; 300 females, 130 males) recruited via Google Forms. Data were collected using the Personal Information Form, Self-disclosure Scale, Satisfaction with Life Scale, and Positive and Negative Affect Scale. Significant differences in self-disclosure were found based on place of residence, with metropolitan residents reporting higher self-disclosure levels than village residents. However, self-disclosure did not significantly differ by gender, age, or income level. A significant positive relationship was found between self-disclosure and life satisfaction, as well as self-disclosure and positive emotions. Besides, negative emotions were negatively correlated with self-disclosure and life satisfaction. Income was positively associated with life satisfaction but did not significantly influence self-disclosure behaviors. The findings suggest that self-disclosure is an important factor in emotional well-being and life satisfaction. The significant impact of place of residence on self-disclosure highlights potential environmental influences on communication patterns. Additionally, the positive associations between self-disclosure, positive emotions, and life satisfaction emphasize the role of open self-expression in psychological well-being. Future research can explore these relationships using longitudinal and cross-cultural methods to better understand the underlying mechanisms.
Keywords: Self Disclosure; Life Satisfaction; Emotions; Positive Emotions; University Students